Comparative study on the physicochemical properties of pea, chickpea, and wheat starch gels in the presence of sweeteners. (7th March 2017) - Xing, Qinhui; Hou, Chuanli; Zhang, Zhengmao; Han, Ke; Yan, Qiaozhen; Luo, Jia
Abstract : The physicochemical properties of pea, chickpea, and wheat starch mixed with different sweeteners, namely, glucose, sucrose, maltitol, and oligofructose, at different sweetener/starch ratios of 0, 5, 10, and 20% (w/w) were investigated. The gelatinization temperatures ( T o, T p, and T c ) of the starches increased significantly ( p  < 0.05) with the addition of sweeteners. The effect of sweeteners on raising gelatinization temperatures followed the order: oligofructose > maltitol > sucrose > glucose > control (water alone). Based on the different combinations, the enthalpy of the three starches increased, remained unchanged, or decreased. Rapid viscosity analyzer (RVA) measurements showed that sucrose, oligofructose, and maltitol were more effective in raising the peak viscosity of starches than glucose. Breakdown and setback were decreased significantly in glucose–starches combinations. Texture profile analysis (TPA) revealed that sweeteners increased the hardness of starch gels to varying degrees as compared to the control. In all cases, the pea and chickpea starch were more sensitive to the addition of sweeteners during paste formation than wheat starch, which might be attributed to the higher amylose content in legume starches. The molecular size and number of hydroxyl groups of the sweeteners should be highly considered in discussing the physicochemical changes of the starches. The results provide new evidence for the effect of sweeteners on starch gelatinization and for the development of sugar‐free starch food.